2021
DOI: 10.5194/acp-2021-644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of regional CO<sub>2</sub> contributions at the high Alpine observatory Jungfraujoch by means of atmospheric transport simulations and δ<sup>13</sup>C

Abstract: Abstract. Understanding of regional greenhouse gas emissions into the atmosphere is a prerequisite to mitigate climate change. In this study, we investigated the regional contributions of carbon dioxide (CO2) at the location of the high Alpine observatory Jungfraujoch ("JFJ", Switzerland, 3580 m a.s.l.). To this purpose, we combined receptor-oriented atmospheric transport simulations for CO2 concentration in the period of 2009–2017 with stable carbon isotope (δ13C-CO2) information. We applied two Lagrangian pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 60 publications
(105 reference statements)
2
8
0
Order By: Relevance
“…15, C), which Zobitz et al, (2006) reported as an acceptable uncertainty level. For further comparison, Pieber et al, (2021) filter their multi-year data to exclude CO2 variations < 3 ppm and cluster their data for intercept uncertainties of 1, 2, 3 and 4 ‰, which indicates the performance of their instrument is superior to that of the Delta Ray system presented here. Zobitz et al, (2006) model the improvement in the uncertainty of the intercepts with improvement of the measurement precision for isotope ratios.…”
Section:  13 C-co2 Observations Of the Delta Ray During Deployment At Bhdmentioning
confidence: 99%
See 4 more Smart Citations
“…15, C), which Zobitz et al, (2006) reported as an acceptable uncertainty level. For further comparison, Pieber et al, (2021) filter their multi-year data to exclude CO2 variations < 3 ppm and cluster their data for intercept uncertainties of 1, 2, 3 and 4 ‰, which indicates the performance of their instrument is superior to that of the Delta Ray system presented here. Zobitz et al, (2006) model the improvement in the uncertainty of the intercepts with improvement of the measurement precision for isotope ratios.…”
Section:  13 C-co2 Observations Of the Delta Ray During Deployment At Bhdmentioning
confidence: 99%
“…The potential for field-deployable, laser-based instruments measuring both mole fractions and isotope ratios in atmospheric CO2 in real-time has been demonstrated (Bowling et al, 2003;Mohn et al, 2007). Continuous technical improvement of both analysers and applied calibration techniques enables an achievable measurement precision that is increasingly comparable to that of well-performing IRMS systems (Tuzson et al, 2011;Griffith et al, 2012;Sturm et al, 2013;Hammer et al, 2013;Flores et al, 2017;Pieber et al, 2021) and is approaching the compatibility goal of the World Meteorological Organisation (WMO), (Steur et al, 2021). With that, laser-based instruments may be an interesting alternative for observations that were previously limited to IRMS laboratories and flask sampling programmes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations